2019
DOI: 10.3389/fpsyt.2018.00734
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Increases Expression of 5-HT2B Receptors in Astrocytes Thus Enhancing Action of Fluoxetine on the Depressive Behavior Induced by Sleep Deprivation

Abstract: The long-lasting loss of sleep is a generally acknowledged risk factor for the occurrence of major depressive disorder (MDD), whereas sleep abnormalities being a key clinic symptom of the MDD. In our previous work, we demonstrated that the sleep deprivation (SD) stimulates activation of nucleotide-binding domain and leucine-rich repeat protein-3 (NLRP3) inflammasomes as well as the release of IL-1β and IL-18 from astrocytes. However, the underlying mechanism connecting SD and MDD still requires further study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 42 publications
2
56
0
Order By: Relevance
“…Treatment with various concentration of fluoxetine regulates the expression of cFos through the opposite effects of PI3K/AKT and MAPK/ERK signalling pathways in astrocytes. The cFos is a transcription factor which regulates expression of several genes, such as caveolin-1 and BDNF 15,16,37 . Here we found that fluoxetine at 1 M suppressed the expression of ADAR2 increased by alcohol by regulating cFos through Src-mediated transactivation of EGFR and the downstream PI3K/AKT signalling pathway in astrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with various concentration of fluoxetine regulates the expression of cFos through the opposite effects of PI3K/AKT and MAPK/ERK signalling pathways in astrocytes. The cFos is a transcription factor which regulates expression of several genes, such as caveolin-1 and BDNF 15,16,37 . Here we found that fluoxetine at 1 M suppressed the expression of ADAR2 increased by alcohol by regulating cFos through Src-mediated transactivation of EGFR and the downstream PI3K/AKT signalling pathway in astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol abuse, however, can affect not only neuronal networks but also act on astrocytes, which are primarily responsible for homeostasis and catabolism of central neurotransmitters [9][10][11] . According to our previous studies, dysfunction of astrocytes contributes to pathophysiology of MDD, while SSRI antidepressant fluoxetine acts as an agonist of 5-HT2BR in astrocytes; this action being linked to fluoxetine anti-depressive activity [12][13][14][15][16] . Fluoxetine selectively increases the expression of 5-HT2BR in astrocytes, and up-regulates 5-HT2CR expression in neurones in conditions of chronic unpredictable mild stress (CUMS) 17 .…”
Section: Introductionmentioning
confidence: 94%
“…Proper physical exercise would prevent the induction of inflammasome . Sound sleep also helps to keep inflammasome quiescent . Confronting the aging‐related CNS diseases, targeting inflammasome is a promising therapeutic strategy.…”
Section: Targeting Inflammasome To Retard the Pace Of Aging And Brakementioning
confidence: 99%
“…88 Sound sleep also helps to keep inflammasome quiescent. 89 Confronting the aging-related CNS diseases, targeting inflammasome is a promising therapeutic strategy. A broad body of F I G U R E 4 Interactions of inflammasome in microphage with neural inflammation and aging-related diseases.…”
Section: Targ E Ting Infl Amma Some To Re Tard the Pace Of Ag Ing Amentioning
confidence: 99%
“…The 5-HT2BRs are related to the major depressive disorder (MDD); these receptors expressed in astrocytes are targets for serotonin-specific re-uptake inhibitors (SSRIs) (Li,5 Zhang, Li, Hertz, & Peng, 2009;Li, Zhang, Zhang, Hertz, & Peng, 2011;Li et al, 2008;Li et al, 2018;Peng, Gu, Li, & Hertz, 2014;Peng, Song, Li, & Verkhratsky, 2018).…”
Section: Introductionmentioning
confidence: 99%